Composing interactive music : techniques and ideas using Max - Winkler, Todd, 1958- (MIT Press, 1998)
Interactive music refers to a composition or improvisation in which software interprets live performances to produce music generated or modified by computers. In Composing Interactive Music, Todd Winkler presents both the technical and aesthetic possibilities of this increasingly popular area of computer music. His own numerous compositions have been the laboratory for the research and development that resulted in this book. The author's examples use a graphical programming language called Max. Each example in the text is accompanied by a picture of how it appears on the computer screen. The same examples are included as software on the accompanying CD-ROM, playable on a Macintosh computer with a MIDI keyboard. Although the book is aimed at those interested in writing music and software using Max, the casual reader can learn the basic concepts of interactive composition by just reading the text, without running any software. The book concludes with a discussion of recent multimedia work incorporating projected images and video playback with sound for concert performances and art installations. -- Provided by publisher.